IN THE REALM OF THE CENSUS. - RICHARDSON, SARAH (American History, 2018)
The article discusses the career of inventor Herman Hollerith and his work on managing census data. It mentions his work with a punch card system to tabulate census data, his processing of data from the 1890 census which proved his technique and his found of the Tabulation Machine Company to build the devices to read the punched cards.